Legal Review of the Misuse of Voice Changer Technology in the Dissemination of Hoaxes and Information Manipulation in Indonesia - Satriya Nugraha; Rengga Kusuma Putra; Aziz Widhi Nugroho; Retno Eko Mardani; Rosmawiah Rosmawiah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The spread of hoaxes through voice manipulation technology, such as voice changers, has become a significant issue in Indonesia in recent years. This technology allows perpetrators to manipulate someone's voice, which is then used to spread false information that can damage an individual's reputation, influence public opinion, and create social unrest. This study aims to analyze the legal aspects related to the misuse of voice changers in the spread of hoaxes, identify the challenges faced in law enforcement, and provide policy recommendations to improve legal protection for hoax victims. The methodology used in this research is normative legal research, with a normative approach focusing on the analysis of the Electronic Information and Transactions Law (UU ITE) and the Personal Data Protection Law (UU PDP), as well as other relevant regulations. The results show that although Indonesia has a sufficient legal framework to address hoax cases involving voice changers, law enforcement still faces challenges in terms of identifying perpetrators, proving voice manipulation, and the lack of more specific regulations. Additionally, victims have the right to legal protection, including compensation and clarification of false information. This study recommends enhancing the capacity of law enforcement, strengthening regulations, and improving digital literacy among the public to address the challenges posed by this technology.